LATIHAN SQUAT DAN STIMULASI TRANSCUTANEUS ELECTRICAL NERVE STIMULATIONS PADA KONDISI PASCA REKONSTRUKSI RUPTUR ANTERIOR CRUCIATE LIGAMENT RUPTURE: SEBUAH LAPORAN KASUS - Febby Arianti; Slamet Sumarno; Lucky Anggiat (Jurnal Kesehatan dan Fisioterapi, 2023)
The most common injuries in futsal games are lower limb injuries. Anterior cruciate ligament (ACL) injuries that occur in futsal players are when the player is running suddenly stopped then rotates in a direction that causes the knee to be pulled and twisted. The tear of ACL that more than 60% or total tears can cause knee joint instability. Patient must undergo surgery to replace the rupture ligament to prevent instability in the knee joint. Squat exercise will affect the increase in muscle strength, proprioceptive function, and functional ability of the knee joint and pain relief modality with Transcutaneous Electrical Nerve Stimulation. The research method used was a case study in a patient with a post-reconstruction ACL rupture condition three weeks after surgery. From the results of basic motion examinations and functional examinations and patient complaints the problem in framework of impairment were knee flexion pain, decreased range of motion (ROM). Then, in functional limitation, the patient was complaining impaired walking. Then, in the framework of participation restriction, patients cannot work as radiographers, doing futsal as a hobby and praying. Patient with post-reconstruction ACL rupture condition showed that there was decreased ROM, active and passive motion pain, decreased muscle strength and decreased functional ability. The closed kinetic chain exercise approach with squat exercise and the addition of TENS can provide good results in the results of increased LGS, reduction of motion pain and increased functional ability.Keywords: Physiotherapy, Exercise Therapy, ACL Rupture, TENS